Theoretical Review Study: Peran Dan Fungsi Mutu Pelayanan Kesehatan Di Rumah Sakit - Wo'i Megah Mayang Sari Paraisu; Dety Mulyanti (Universitas Katolik Widya Karya Malang, 2023)
The roles and functions of quality management, known as total management quality, can be interpreted as a system that helps an organization, hospital, or business entity to oversee every activity and duties and responsibilities needed to maintain the quality or quality of service. Efforts to improve the quality of health services are the most important step to increase the competitiveness of Indonesian businesses in the health sector. The purpose of this theoretical review study is to find out how the role and function of the quality of health services in hospitals. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review study are the role and function of quality as an effort that is carried out continuously, systematically, objectively, and integratedly in determining problems and causes of health service quality problems based on predetermined standards with effectiveness, efficiency, protection and acceptance of health services. It can be concluded that service quality and good quality will greatly influence health services in hospitals. Patients getting comprehensive health services will increase patient satisfaction in the treatment program so that the quality of health services will increase. Hospitals also need to improve the quality of quality health services. Quality also has a function as a reference or benchmark in managing the quality provided by a hospital. So that in its implementation it is necessary to carry out monitoring and evaluation.